Characteristics of Gel Emulsion Formulation of Snakehead (Channa Micropeltes) As Wound Healer - Firlianty Firlianty; Choirul Anwar; Anang Najamuddin; Silvester B. Pratasik (Fisheries and Marine Science Faculty - Jenderal Soedirman University)
This study is aimed to know the characteristics and the effectivity of gel emulsion of snakehead (Channa micropeltes) extract in accelerating wound healing process. It used experimental method with Complete Randomized Design. Four treatments with 3 replications were employed, i.e. 1%, 2%, and 4% gel emulsion of snakehead Channa micropeltes extract and a control treatment. Results showed that C. micropeltes extract formulated in gel emulsion had white colour, typical aroma of gel emulsion, soft texture with mean dispersion ability of 3 cm, and pH 6. In vivo test on male mices that gel emulsion of C. micropeltes extract was highly effective (P≤0.05) to accelerate wound healing, in which the treatment of 1% gel emulsion gave the highest effect with 98.5% wound healing at day-14, followed with that of control treatment, 95% healing, then 2%, 90% healing and 4%, 90% healing, respectively. Snakehead (Channa micrpeltes) extract formulated in gel emulsion can speed up the wound healing process.